Saccharomyces cerevisiae Is Permissive for Replication of Bovine Papillomavirus Type 1 - Zhao, Kong-Nan (American Society for Microbiology, 2002)
We recently demonstrated that Saccharomyces cerevisiae protoplasts can take up bovine papillomavirus type 1 (BPV1) virions and that viral episomal DNA is replicated after uptake. Here we demonstrate that BPV virus-like particles are assembled in infected S. cerevisiae cultures from newly synthesized capsid proteins and also package newly synthesized DNA, including full-length and truncated viral DNA and S. cerevisiae-derived DNA. Virus particles prepared in S. cerevisiae are able to convey packaged DNA to Cos1 cells and to transform C127 cells. Infectivity was blocked by antisera to BPV1 L1 but not antisera to BPV1 E4. We conclude that S. cerevisiae is permissive for the replication of BPV1 virus.